The Effect of Price and Product Quality on Customer Satisfaction in UMKM Bakso Berkah Berjaya - Anda Yanny; Ronda Deli Sianturi (Institute of Computer Science (IOCS), 2022)
UMKM Berkah Berjaya is a Home Industry for making raw meatballs. With a tool that is still simple, but can continue to operate even though the Covid-19 Pandemic hits. The price is quite affordable and the taste that is not inferior to branded packaging products is supported by cleanliness during the manufacturing process making this business even more successful. This research wanted to see how much influence price and product quality have on customer satisfaction. The results of the research that the author conducted using SPSS 20 obtained results from 40 respondents in the form of fixed customers, that price affects customer satisfaction. Product quality also affects customer satisfaction. Simultaneously also the price and quality of the product affect customer satisfaction.